General perception and self-practice of complementary and alternative medicine (CAM) among undergraduate pharmacy students of Bangladesh - Bijoy Laxmi Saha; Md. Omar Reza Seam; Md. Mainul Islam; Abhijit Das; Sayed Koushik Ahamed; Palash Karmakar; Md. Fokhrul Islam; Sukalyan Kumar Kundu (BMC, 2017)
Abstract Background Complementary and Alternative Medicine (CAM) is a combination of herbal medicine, traditional therapies, and mind-body intervention. This descriptive study was designed to assess the knowledge, attitudes, perception and self-use of CAM among Bangladeshi undergraduate pharmacy students. The study also evaluated their opinions about its integration into the pharmacy course curriculum. Methods It was a cross-sectional, questionnaire-based study conducted on 250 pharmacy students of five reputed public universities of Bangladesh. Results This study revealed that majority of the pharmacy students were using or had previously used at least one type of CAM. Among the students, 59% had used homeopathy followed by Ayurveda (30%), meditation (29%), massage (13%), Unani (9%), yoga (6%) and acupuncture (2%). Students' attitudes towards CAM were influenced by family and friends, books and journals, the internet and to a lesser degree by health practitioners. A significant (p < 0.05) number of students had knowledge about CAM. A majority of the students (90%) had positive, while 10% had negative attitudes towards CAM. Lack of knowledge and trained professionals were found to be the major interruptions to CAM use. 84.45% acknowledged the importance of knowledge about CAM for them as future healthcare practitioners. Furthermore, the majority of the students also believed that ideas and methods of CAM would be beneficial for conventional medicine. Conclusions From the findings of the study, it can be recommended that an approach should be taken to educate the students about the fundamentals of CAM use so that it may fulfill the professional needs of our future pharmacists.